2004
DOI: 10.1074/jbc.m402576200
|View full text |Cite
|
Sign up to set email alerts
|

Acute Formation of Protease-resistant Prion Protein Does Not Always Lead to Persistent Scrapie Infection in Vitro

Abstract: Transmissible spongiform encephalopathies are accompanied by the accumulation of a pathologic isoform of a host-encoded protein, termed prion protein (PrP). Despite the widespread distribution of the cellular isoform of PrP (protease-sensitive PrP; PrP-sen), the disease-associated isoform (protease-resistant PrP; PrPres) appears to be primarily restricted to cells of the nervous and lymphoreticular systems. In order to study why scrapie infection appears to be restricted to certain cells, we followed acute and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 43 publications
6
79
0
Order By: Relevance
“…This most likely contributes to the lack of infection of murine SN56 cells by hamster 263K scrapie. However, acute new PrP-res formation can be initiated after exposure of cells to scrapie without leading to sustainable PrP-res formation (Vorberg et al, 2004). Thus, the establishment of persistent cellular scrapie infections would appear to have requirements beyond simple exposure of cells to exogenous PrP-res and acute conversion of endogenous PrP-sen.…”
Section: Prp-res Uptake Versus Establishing a Sustained Infectionmentioning
confidence: 99%
“…This most likely contributes to the lack of infection of murine SN56 cells by hamster 263K scrapie. However, acute new PrP-res formation can be initiated after exposure of cells to scrapie without leading to sustainable PrP-res formation (Vorberg et al, 2004). Thus, the establishment of persistent cellular scrapie infections would appear to have requirements beyond simple exposure of cells to exogenous PrP-res and acute conversion of endogenous PrP-sen.…”
Section: Prp-res Uptake Versus Establishing a Sustained Infectionmentioning
confidence: 99%
“…The hippocampal cell line HpL3-4 derived from PrP 0/0 mice (29) was transduced with retroviral particles coding for murine PrP tagged with the epitope for the monoclonal antibody 3F4 (Mo3F4 PrP). This epitope can be introduced into murine PrP by the substitution of two amino acid residues at positions L108M and V111M (37) and allows for the discrimination of de novo formed PrP Sc from PrP Sc present in the inoculum (36). Western blot analysis of cells harvested 10 passages after transduction revealed that transduced cells expressed high amounts of Mo3F4 PrP (Fig.…”
Section: Efficient Transduction Of Hippocampus-derived Prp-deficient mentioning
confidence: 99%
“…For fast, efficient, and stable expression of cellular prion protein in the PrP knock-out cells, a retroviral expression system was utilized (36). The hippocampal cell line HpL3-4 derived from PrP 0/0 mice (29) was transduced with retroviral particles coding for murine PrP tagged with the epitope for the monoclonal antibody 3F4 (Mo3F4 PrP).…”
Section: Efficient Transduction Of Hippocampus-derived Prp-deficient mentioning
confidence: 99%
See 1 more Smart Citation
“…PrP C appears to be not the sole determinant factor for prion susceptibility, and other cellular factors may be involved in efficient infections. Under certain conditions, loss of host factors for susceptibility to prion infection may occur [9,54,133]. Furthermore, most cell lines have restricted prion strain specificity, i.e., matching pairs between the host cell and prion strain.…”
Section: Usefullness Of Cell Lines For Studying Prion Infectionsmentioning
confidence: 99%